Clinical Profile, Etiology and In-hospital Outcome of Acute Pancreatitis: Experience at a Tertiary Care Center, Bangladesh (Bangladesh Journal of Medicine, 2024)
Background: Acute pancreatitis (AP) is a potentially life-threatening disease with varying clinical presentations influenced by etiology, social factors, cultural habits, and patient characteristics. Aim: To assess the demographic profile, etiology and in-hospital outcomes of Acute pancreatitis patients. Methods: This prospective observational study was conducted in Department of Medicine, Sir Salimullah Medical College Mitford Hospital, Dhaka from January 2023 to December 2023 after obtaining ethical clearance from ethical review board. We enrolled 107 AP patients diagnosed according to the revised Atlanta classification (2012). Demographics, clinical presentations, risk factors, laboratory data, and imaging findings were collected using a structured questionnaire. All the data were compiled and sorted properly and analyzed by using IBM SPSS, Version 26.0. Results: The mean age was 52.09±14.94 years, with male predominance (66.4%). In this study we found common presentations are abdominal pain (100%), nausea/vomiting (91.6%), and abdominal distension (44.9%). Our study revealed, main etiologies were alcohol consumption (35.5%) and gallstones (34.6%). We observed common comorbidities included diabetes mellitus (42.1%) and hypertension (35.5%). The mean hospital stay was 6.77±1.51 days. Most patients (77.6%) achieved good recovery, while 22.4% had partial recovery. Only 3.7% required ICU care, with no mortality reported. Conclusion: In our study, acute pancreatitis predominantly affected middle-aged males, with alcohol and gallstones being the leading causes. Most patients had good outcomes with conservative management, suggesting effective treatment protocols was follows at our center.Bangladesh J Medicine 2025; 36: 32-36